Penyelesaian Model Epidemiologi SIR Menggunakan Metode Runge-Kutta Orde Tiga Dan Metode Adams-Bashforth Orde Tiga - Hadisusanto, Jeannie; Mungkasi, Sudi (Journal of Mathematics, Computations and Statistics, 2023)
Mathematical modeling can be used to solve problems in everyday life, one of which is beingable to predict situations that occur in the spread of infectious diseases. The model used is the SIRepidemiological model with constant vaccination. In this paper, the model was solved numerically usingthe third order Runge-Kutta method and the third order Adams-Bashforth method. The solutions of the twomethods were obtained with the help of the MATLAB program in the first to tenth iterations. The solutionsshown by the two methods have almost the same behavior in the number of populations that are susceptibleto disease, the number of populations infected with the disease, and the number of populations that haverecovered from the disease. Over time, the number of populations that are susceptible to disease willcontinue to decrease, while the number of people recovering from disease will continue to increase.Meanwhile, the number of population infected with the disease will gradually increase at first and thenwill continue to decrease.